Thinking (a Feminist) History: the Regulation Approach as Theatre - Jenson, Jane (Cahiers de recherche sociologique)

(untitled) (Département de sociologie - Université du Québec à Montréal, 1991)
SummaryThe approach elaborated here is derived from feminist analyses which take seriously the notion that gender relations are social constructions. Using the metaphor of theatre, the article proposes an analysis which takes meaning systems as well as practices seriously. From this point of view, both the mode of regulation and the societal paradigm depend upon actors' strategies in creating their representational systems and thereby constructing their collective identities. Besides, contrary to studies that reduce regulation to the wage relation, this analysis points to the importance of many different political organisations and identities. In so doing, the argument provides a way of understanding why it is that some historical times are more open to recognising marginalised actors' demands for greater power while other moments ignore their claims by silencing their voices.